(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
With the advent of new emerging tech nologies like fog computing, internet of things, blockchain, artificial intelligence etc, information and communication technology is revolutionising our homes, education, health and industry. By the year 2025, with the increase in net work speed offered by 5G technology, we will be able to share much more data in real time. It’s not only important to note that the volume of data shared in future will be huge but also its important to understand that the shared data will be heterogenous in nature. Not only humans but smart devices will act as humans on the network and will generate big data. Thus, the future of cloud storage indus try seems to be very bright. The effort in this paper is to recognise the issues and challenges that the cloud storage industry will face in the near future and also to identify and review the new paradigm for researchers in the field of cloud storage.